The Effect of Functional Value to Revisit Intention Dufan Ancol: the Mediating Role of Customer Satisfaction and Destination Love - Nisa Ajshari; Yadi Ernawadi (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of the perceived value dimension on revisit intention through customer satisfaction and destination love of Dufan Ancol tourists. This study uses a quantitative approach with a survey method involving 140 tourists who have visited Dufan Ancol. Cross-sectional methods are used in data collection. The research instrument has been declared to have passed the validity and reliability test. The data analysis technique used is structural equation modeling based on Smart PLS 3.0. The results of the study show that functional value has a positive effect on revisit intention through customer satisfaction. The findings of this study are expected to help Dufan Ancol managers in prioritizing increasing functional value to increase customer satisfaction so as to encourage revisit intention. Researchers are then advised to test other variables relevant to the characteristics of the research object to gain a more comprehensive understanding of the factors that can influence revisit intention.